IMPLEMENTASI MODEL PEMBELAJARAN COOPERATIVE SCRIPT DALAM PERKULIAHAN TEORI & PRAKTIK PEMBELAJARAN MENYIMAK SEBAGAI UPAYA PENINGKATAN PRESTASI, AKTIVITAS, DAN KETERAMPILAN BERBICARA PADA MAHASISWA - Nurhayatin, Titin; Triandy, Rendy (STKIP Subang, 2019)
This study aims to determine the effectiveness of the application of cooperative script learning models in lectures Theory & Practice of Listening Learning as an effort to improve student achievement, activities, and speaking skills. Listening skills are one of the important language skills to be mastered by students, so appropriate strategies or learning models are needed in their application. The research method used in this study is an experimental research method with a pretest-posttest control group design research design. The population in this research were students programme of study in the Indonesian Language and Literature Education  FKIP Unpas. The sample in this study was the first semester students Programme of Study in the Indonesian Language and Literature Education FKIP Unpas. Based on the results of data processing using the SPSS 25 application, the value of sig is obtained. (2-tailed) of 0,000 <0.05. This shows that Ha was accepted and Ho was rejected. Therefore, it can be interpreted that the learning outcomes, activities, and speaking skills of semester I students programme of study in the Indonesian Language and Literature Education FKIP Unpas increased in lectures on Theory and Practice of Listening Learning using Cooperative Script learning models.